Method for preparing silicon anode solid electrolyte composite, solid-state lithium ion battery cell

By depositing a multi-layer structure on the solid electrolyte as the active layer of the silicon anode and controlling the energy input through rapid annealing, the problem of difficulty in contact between the solid electrolyte and the anode is solved, and efficient improvement of ionic conductivity and battery performance is achieved. .

CN119404321APending Publication Date: 2025-02-07NORCSI GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380046837.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-20
Filing Date
2023-02-08
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The contact between the solid electrolyte and the anode is difficult to achieve effective ionic conductivity, resulting in a degradation of battery performance, and high crystallinity requires a high temperature process, affecting the integrity of the battery assembly.

Method used

The dry deposition method is used to deposit multi-layer structures as the active layer of the silicon anode on the porous solid electrolyte, and control energy input through rapid annealing to achieve stable intermediate layer deposition between the anode active layer and the solid electrolyte, and reversely manufacture the silicon anode -Solid electrolyte linker.

Benefits of technology

Optimal ionic contact with solid electrolyte is achieved, improving cell performance and stability, reducing weight and layer thickness, while reducing manufacturing costs and complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404321A_ABST
    Figure CN119404321A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing a planar silicon anode-solid electrolyte composite suitable for use in a solid-state battery and to a planar silicon anode-solid electrolyte composite produced thereby. The object of the invention is to provide a method for producing a silicon anode-solid electrolyte composite which ensures consistent, good electrical contact between cell layers, said object being achieved by a method for producing a planar silicon anode-solid electrolyte composite suitable for use in solid-state cells, wherein a multilayer structure, which is an active layer of a silicon anode, is deposited on a porous solid electrolyte by a dry deposition method, in which the multilayer structure is rapidly annealed and a current collector, preferably made of copper, is deposited on the multilayer structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a planar silicon anode-solid electrolyte interconnector suitable for solid-state batteries, and to a planar silicon anode-solid electrolyte interconnector produced thereby.

[0002] The invention further relates to a solid-state battery cell comprising a cathode and the inventive planar silicon anode-solid electrolyte interconnect, and to a solid-state battery comprising at least one solid-state battery cell. Background Art

[0003] As an introduction, some of the principles related to batteries as electrochemical energy storage and the associated terminology used are reiterated and defined.

[0004] Batteries are electrochemical energy storage devices and are divided into primary batteries and secondary batteries.

[0005] Primary batteries are electrochemical energy sources that irreversibly convert chemical energy into electrical energy. Therefore, primary batteries are not rechargeable. On the other hand, secondary batteries, also known as accumulators, are rechargeable electrochemical energy storage devices in which the chemical reactions that occur are reversible and can be used multiple times. During charging, electrical energy is converted into chemical energy, and during discharge, chemical energy is converted back into electrical energy.

[0006] A "battery" is a device of interconnected battery cells. A cell is an electrochemical device consisting of two electrodes, an electrolyte, a separator, and a battery casing. Figure 1 The schematic structure and function of a lithium-ion cell during discharge are shown. Each lithium-ion cell consists of two different electrodes 7, 9: an electrode 9 that is negatively charged in the charged state and an electrode 7 that is positively charged in the charged state. Since the release of energy (in other words, the discharge) is accompanied by the migration of ions from the negatively charged electrode to the positively charged electrode, the positively charged electrode is called the cathode 7 and the negatively charged electrode is called the anode 9. Each electrode consists of a current collector 2, 8 and an active material coated thereon. Located between the electrodes is firstly an ion-conducting electrolyte 4, which enables the required charge exchange, and a separator 5, which ensures the electrical separation of the electrodes.

[0007] The main difference between solid-state batteries, or solid-state batteries, and traditional batteries is the solid electrolyte. The role of the electrolyte is to conduct ions between the anode and cathode.

[0008] Battery cells can be connected in different ways. If two battery cells are connected in series, the anode (negative pole) of one battery cell is connected to the cathode (positive pole) of the other battery cell during discharge. When battery cells are connected in series, the total voltage is increased: the voltages of the individual cells are added. If battery cells are connected in parallel, all cathodes (positive poles) are connected to one another, as are all anodes (negative poles) (in the case of discharge). In the parallel connection of cells, the capacity (Ah) of the battery is doubled. The same applies to the parallel connection of batteries to form battery modules.

[0009] In currently available lithium-ion batteries, liquid electrolytes are used in order to utilize lithium between the electrodes (anode and cathode) to store and release energy. Since aqueous electrolytes have a low potential window for stable operation, organic solvents are used. However, these solvents are highly flammable, increasing the risk of fire in the battery. The use of solid electrolytes with significantly lower flammability is seen as a solution. Solid electrolytes have good ionic conductivity and good electrical insulation, and can replace existing liquid electrolytes and separators. At the same time, when solid electrolytes are used, the volume and weight are reduced by increasing the energy density (especially when metallic lithium is used), so the packing density can be significantly increased.

[0010] However, the disadvantage of solid electrolytes is that they are less flexible and difficult to contact with the anode and cathode to obtain effective ionic conductivity. For good battery performance, surface contact between the anode and the solid electrolyte is crucial. In particular, for ceramic electrolytes with powdered raw materials (e.g., consisting of sintered powders) and high surface porosity, limited ionic contact at the boundary layer between the cathode-electrolyte or electrolyte-anode may significantly reduce the performance of the battery. In addition, in the case of high surface currents, lithium metal forms dendrites with the solid ceramic electrolyte, which can damage the battery. In addition, lithium reacts with the surface of the solid electrolyte, resulting in a decrease in ionic conductivity during operation. Various known methods for improving electrical contact include: adding liquid electrolytes, softening / mixing solid electrolytes by polymers and / or binders, or using relatively soft sulfur-based solid electrolytes, such as lithium argyrodite. Argyrodite is a solid compound rich in lithium. The argyrodite family consists of more than 100 crystalline solids and extends to solid compounds in which, for example, silver is replaced by copper, germanium is replaced by gallium or phosphorus, and sulfur is replaced by selenium. Alternatively, high pressure can be used, which is particularly necessary for the volume expansion that occurs during battery operation in order to ensure continuous contact. However, the high pressures required for this purpose are usually associated with high costs and complexity for commercial structures.

[0011] Therefore, in order to achieve effective ionic conductivity within the solid electrolyte, a high degree of crystallinity is generally required, with corresponding defects in the lattice. For oxide-based materials, such as lithium lanthanum zirconium oxide (LLZO) garnet crystals, this requires very high crystallization temperatures, which are much higher than the temperatures allowed to maintain the integrity of other battery components, especially the anode. Therefore, when constructing the solid electrolyte-anode connector, it is necessary to first perform the process steps involving the highest required temperature and then reduce the temperature as required. Therefore, with regard to the construction of the solid electrolyte-anode connector, it is necessary to first produce the solid ceramic electrolyte, then construct the anode, and finally deposit the copper current collector. For graphite-based anodes, it is known from the prior art to deposit such battery graphite on the anode side of the separator; however, this is mainly used to control / prevent the sulfur shuttling effect in lithium-sulfur batteries. Summary of the invention

[0012] It is therefore an object of the present invention to provide a method by which a silicon anode-solid electrolyte interconnect can be produced which overcomes the above-mentioned disadvantages.

[0013] Another object of the present invention is to provide a solid-state battery cell or a solid-state battery which does not have the above-mentioned disadvantages.

[0014] This object is achieved by a method according to the independent method claim 1 .

[0015] In a method for making a planar silicon anode-solid electrolyte interconnect suitable for solid-state batteries, a multilayer structure is deposited as an active layer of a silicon anode onto a porous solid electrolyte by dry deposition, the multilayer structure is rapidly annealed, and a current collector preferably composed of copper is deposited on the multilayer structure.

[0016] A porous solid electrolyte is understood to be a layer of sintered powder. The powder is formed by pressing a ceramic into a layered structure and heating it.

[0017] A multistratum structure is understood to be a stratified structure consisting of two or more strata, but in the disclosure of the present invention, the term "multistratum structure" also includes a single stratum.

[0018] The method of the invention is particularly suitable for preparing battery cells for various different battery applications, because the method enables a complete and planar granular solid electrolyte-silicon anode structure to be achieved with additives that stabilize the multilayer structure of the anode active layer. By using dry manufacturing processes, such as sputtering or electron beam evaporation, not only can the multilayer structure be deposited directly on the solid electrolyte as the active layer of the anode, but also additional intermediate layers can be applied to stabilize the solid electrolyte / anode interface without additional cost and complexity. Rapid annealing allows targeted control of the energy input into the layer.

[0019] In one embodiment of the method according to the invention, an intermediate layer for stabilization between the solid electrolyte and the active layer of the silicon anode is deposited between the solid electrolyte and the multilayer structure.

[0020] Particularly advantageously, the silicon anode-solid electrolyte interconnect is produced in the reverse order compared to existing methods. The anode can thus be applied directly to the solid electrolyte, thus enabling optimal ionic contact with the normally difficult-to-access solid electrolyte.

[0021] If the manufacturing method starts with a solid electrolyte, the current collector can be optimized on the anode side so that it no longer has to assume any necessary load-bearing functions. The material thickness of the copper current collector can thus be reduced to the current density actually required in the application, thereby reducing weight and layer thickness without any adverse effects on the thermal transport of heat. Overall, a significant weight reduction and thus an increase in gravimetric energy density can be achieved.

[0022] The planar deposition process in the dry deposition method means that the manufacturing method of the present invention guarantees a consistent layer structure. The basic process steps result in a large number of parameters that can be optimized in a targeted manner for the respective application. In particular, the key advantage of a targeted energy input can be achieved through rapid annealing. Through rapid annealing, the energy input can be controlled layer by layer (stratumby stratum), thereby achieving the full functionality from silicon anode to all-solid-state battery (ASSB).

[0023] Therefore, in another embodiment of the method according to the invention, the multilayer structure is deposited layer by layer, wherein the multilayer structure is formed from at least one layer of metal and / or silicon or a mixed system consisting of silicon mixed with at least one metal.

[0024] The multilayer structure is formed by at least one stratum. A stratum is a deposited layer of anode active material; depending on the thickness of the layer, the active layer of the electrode / anode can consist of one or more layers. At least one layer can be formed on the one hand from at least one metal and / or silicon. In this case, silicon and at least one metal are applied alternately by layered deposition of the materials. Thus, a stratum is formed from at least one layer of at least one metal and one layer of silicon; in order to achieve the target thickness of the anode, the multilayer structure contains a plurality of layers. Alternatively, at least one stratum can also be formed from a mixed system consisting of silicon mixed with at least one metal. This mixture of at least one metal and silicon is usually deposited in powder form until the active layer has reached its target thickness.

[0025] The insertion of lithium is accompanied by volume expansion, but due to the metal doping and the use of a multilayer structure, the silicon layer of the silicon anode does not pulverize. Compared with pure silicon, metal doping leads to the formation of an alloy, so the hardness is reduced. At the same time, the electrical conductivity of silicon is significantly improved compared to graphite. Despite the metal doping, a total specific capacity of more than 2000mAh / g can be ensured.

[0026] The stability and high conductivity of silicon anodes are supported by the development of heterostructures that form a conductive matrix of metal or metal silicide surrounding amorphous regions of silicon.

[0027] In one embodiment of the manufacturing method of the present invention, the metal is formed by at least one of the materials manganese (Mn), cobalt (Co), iron (Fe), titanium (Ti), nickel (Ni), aluminum (Al), tin (Sn), gold (Au) and / or silver (Ag) or a mixture of these materials.

[0028] In a different embodiment of the manufacturing method of the present invention, the dry deposition method is a PVD process: for example sputtering. Preferred methods are sputtering and electron beam evaporation. It is also possible to be a CVD (chemical vapor deposition) method (for example plasma enhanced CVD (PECVD)) or a PVD (physical vapor deposition) method (for example thermal evaporation or PLD (pulsed laser deposition) method).

[0029] In another different embodiment of the manufacturing method of the present invention, rapid annealing controls the energy input into the deposited layers of the multilayer structure and / or the silicon anode-solid electrolyte interconnect or the layers of the solid-state battery cell and / or solid-state battery.

[0030] By using rapid annealing, the planar structure of the silicon anode-solid electrolyte interconnect of the present invention can be carried out in the above order (i.e., solid electrolyte-active layer-current collector), or in the reverse order (starting from the current collector, followed by the active layer of the anode, and constructing the solid electrolyte with further processes and / or PVD methods). Since the contact of the solid electrolyte-anode interface is critical to the battery performance, only a thin layer is sufficient to produce a stable contact. The desired crystallinity or ionic conductivity in the solid electrolyte can be achieved by rapid annealing.

[0031] That is, in a different embodiment of the method of the present invention, the method steps for manufacturing a planar silicon anode-solid electrolyte interconnect are performed in reverse order, specifically, the multilayer structure is deposited as an active layer on a current collector (preferably copper) of a silicon anode by a dry deposition method, and then controllable and adjustable energy is input into the multilayer structure of the silicon anode for rapid annealing; an intermediate layer is deposited on the multilayer structure for stabilization between the solid electrolyte and the active layer of the silicon anode; and a solid electrolyte is deposited, which is rapidly annealed to crystallize the solid electrolyte.

[0032] In one embodiment of the manufacturing method of the present invention, the rapid annealing is flash lamp annealing, which can be performed by flash lamp annealing with a duration of 0.2 to 20 ms and an energy density of 0.3 to 160 J / cm 2 The flash lamp is carried out in the range of 4°C to 200°C, and is carried out together with preheating or cooling in the range of 4°C to 200°C.

[0033] In a different embodiment of the manufacturing method of the present invention, the rapid annealing is laser annealing, which can be performed using an annealing time in the range of 0.01 ms to 100 ms and an energy density in the range of 0.1 to 100 J / cm by setting the scanning rate of the local heating site. 2 The treatment is performed with a laser in a range of 4°C to 200°C, and with preheating or cooling in a range of 4°C to 200°C.

[0034] The temperature range from 4° C. to 200° C. refers to the surface temperature of the substrate or the layer to be annealed.

[0035] It has been shown that rapid annealing has different effects on the deposition of different materials in the active layer. This difference is believed to be caused by the different chemical reactions involving silicon. As a result, different structures can be formed in the resulting anode layer, for example, columnar structures for nickel deposition. In addition, different silicides can be formed, which can also intercalate lithium - in contrast to copper silicides, which have little or no ability to intercalate lithium. The advantage of using these differences is that the volume expansion of silicon during lithium insertion can be controlled. As a result, the stability of the battery operation is significantly enhanced.

[0036] For titanium, Ti silicide is formed, which can have Li embedding ability in the right phase (see: Xu, J. et al. Preparation of TiSi2 Powders with Enhanced Lithium-Ion Storage via Chemical Oven Self-Propagating High-Temperature Synthesis. Nanomaterials 11, 2279 (2021)). This has the advantage that there is no clear interface between active lithium and inactive lithium, so there is good electrical contact even during cycling. Other metals (such as aluminum) do not form any compounds with silicon - that is, no silicide is formed. As a result, these metals are mixed into silicon, increasing the conductivity. By a rapid annealing step, the morphology and hardness of the silicon-metal layer can be further improved relative to hard pure silicon.

[0037] The reaction caused by rapid annealing between silicon particles and metal particles in the active layer of the silicon anode is a non-equilibrium process that can only be achieved within a millisecond time range, thus requiring the use of a flash lamp or a laser.

[0038] The heating rate achieved in rapid annealing is within the range of 10 4 -10 7 To this end, flash lamp annealing utilizes a spectrum in the visible wavelength range, while laser annealing uses discrete wavelengths in the infrared (IR) to ultraviolet (UV) spectral range.

[0039] In terms of design, the object of the invention is achieved by a planar silicon anode-solid electrolyte interconnect according to the independent arrangement of claim 10 .

[0040] In the case of the inventive planar silicon anode-solid electrolyte interconnect produced by the method according to the preceding claims 1 to 9, the solid electrolyte preferably consists of an oxide-based material, more particularly of a garnet structured oxide, NASICON-type phosphate glass-ceramics or oxynitride.

[0041] Garnet structured oxides are structurally perovskites, such as the widely studied lithium lanthanum zirconium oxide (LLZO). NASICON-type phosphate glass-ceramics, named for their chemical structure of NaZr2(PO4)3, have high ionic conductivity for lithium ions. Examples include LAGP (lithium aluminum germanium phosphate) and LATP (lithium aluminum titanium phosphate). Nitride oxides are oxides formed by replacing some of the oxygen atoms with nitrogen to produce many defects in the lattice, and therefore have high ionic conductivity; for example, xLi2O∶yP2O5∶zPON, abbreviated as LiPON. LiPON can be prepared by sputtering Li3PO4 in a reactive N2 plasma.

[0042] The silicon anode-solid electrolyte interconnect of the present invention includes a solid electrolyte, which is realized by an oxide material, in particular by a garnet structure oxide, such as LLZO, NASICON-type phosphate glass ceramics (such as LATP or LAGP) and nitrogen oxides (such as LiPON). In order to achieve effective ionic conductivity, the oxide material requires a high degree of crystallinity and therefore requires a high processing temperature. For a LiPON sputtered layer, the process temperature is in the room temperature range, for a fully crystallized sintered LLZO ceramic, the process temperature is as high as 1230°C, and for the glass transition temperature of NASICON ceramics, the process temperature is about 700°C.

[0043] The above oxide-based materials are particularly suitable for ASSBs because they have an ionic conductivity greater than 1 mS / cm (milli-Siemens / cm) and are very stable both thermally and chemically.

[0044] In a different embodiment of the silicon anode-solid electrolyte interconnect of the present invention, the solid electrolyte has a high crystallinity of ionic conductivity, which can be specifically adjusted by means of rapid annealing.

[0045] Rapid annealing enables the construction of a planar silicon anode-solid electrolyte interconnect of the present invention as described above. Surface contact enables effective ionic conductivity between the active layer of the silicon anode and the solid electrolyte. Artificial SEI, as an intermediate layer between the silicon anode and the solid electrolyte, can further improve the contact between the two layers. Another possibility is poor contact between the silicon anode and the solid electrolyte, manifested as degradation of the solid electrolyte surface, especially in the case of a metallic anode.

[0046] The object of the present invention is also achieved by a solid-state battery cell having a cathode and a planar silicon anode-solid electrolyte interconnect manufactured by using the method according to any one of claims 1 to 9, wherein the silicon anode, the solid electrolyte and the cathode have a planar structure.

[0047] The production of complete solid-state cells or solid-state batteries together with solid electrolytes in a planar deposition method is particularly advantageous, since the planar structure enables the production of solid electrolytes on planar silicon anodes and also enables the application of silicon anodes and copper current collectors directly on the solid electrolyte.

[0048] In another different embodiment of the solid-state battery cell of the present invention, the active layer of the cathode is formed of LiFePO4, LiMnO2 or LiCoO2, and a current collector (preferably composed of aluminum) is formed as a cathode on the active layer.

[0049] Particularly suitable materials for cathodes are those capable of dry deposition. A method known in the prior art is to deposit LiFePO4 layer by layer as a cathode. Specific materials can be prepared in a planar form by sputtering (see: 1. Bünting, A., Uhlenbruck, S., Sebold, D., Buchkremer, HP & Vaβen, R. Three-Dimensional, Fibrous Lithium Iron Phosphate Structures Deposited by Magnetron Sputtering. ACS Appl. Mater. Interfaces 7, 22594–22600 (2015); or 2. Fischer, J. et al. Development of thin film cathodes for lithium-ion batteries in the material system Li–Mn–O by rf magnetron sputtering. Thin Solid Films 528, 217–223 (2013)), which are particularly suitable for manufacturing layer stacks.

[0050] In one embodiment of the solid-state battery cell of the present invention, an anode side structure having a silicon anode-solid electrolyte connector and a silicon anode-copper current collector connection and a cathode side structure having a solid electrolyte-cathode-aluminum current collector connector and / or a cathode electrolyte-aluminum current collector connector can be manufactured and constructed separately from each other, and the silicon anode-solid electrolyte connector and the silicon anode-copper current collector connector and the solid electrolyte-cathode-aluminum current collector connector and / or the cathode electrolyte-aluminum current collector connector are configured in a manner that can be interconnected through respective bulk contacts in the final manufacturing step.

[0051] As a result of the method of the invention, for the first time, the manufacture of the layers in a complete solid-state battery cell can be achieved in a different manufacturing sequence, and it is even possible to manufacture all the components of the solid-state battery cell separately from each other, with the feature that the transition contact has been fully formed. The transition contact refers to, for example, the interface between the silicon anode and the solid electrolyte. Therefore, all that remains is to assemble the materials that are similarly formed. In the anode-side structure, due to the planar structure, for the first time, the active layer of the silicon anode can be applied directly to the solid electrolyte and then the copper current collector is deposited, or the planar active layer is first deposited on the copper current collector and then the solid electrolyte is deposited. For the cathode-side structure, there are already methods for coupling the solid electrolyte and the cathode to each other, that is, the active layer of the cathode is applied to the solid electrolyte and then the aluminum current collector is applied, or the active layer of the cathode is deposited on the aluminum current collector and then the solid electrolyte is deposited. These layer combinations, namely silicon anode-solid electrolyte and / or copper current collector-silicon anode and / or solid electrolyte-cathode-aluminum current collector, can now be manufactured independently of each other to simplify the manufacturing process; in order to manufacture or form a solid-state battery cell, these layer combinations are connected / bonded to each other via their respective block contacts. For example, in the connection between the silicon anode-solid electrolyte and Cu current collector-silicon anode layer combination, the bulk contact refers to the coupling of the active layer part, or in the connection between the silicon anode-solid electrolyte and solid electrolyte-cathode-aluminum current collector layer combination, the bulk contact refers to the coupling through the solid electrolyte. This coupling can optionally be supported by a temperature step.

[0052] The object of the present invention is also achieved by a solid-state battery consisting of a plurality of solid-state battery cells, wherein the plurality of solid-state battery cells are applied flat and stacked together using the provided production method. The contact can be achieved in parallel and / or in series with one another.

[0053] The present invention will be explained in more detail below with reference to exemplary embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] The contents of the figure are as follows:

[0055] Figure 1 An exemplary structure and function of a lithium-ion battery with a liquid electrolyte during discharge is shown (prior art);

[0056] FIG2 shows the sequence of the production method for a silicon anode-solid electrolyte interconnect of the present invention: a) in the following sequence: solid electrolyte-anode; b) in the following sequence: current collector-active layer-solid electrolyte;

[0057] Figure 3 shows the structure of solid-state battery cells and other layers manufactured by stacking battery cell assemblies on each other according to the method of the present invention;

[0058] Figure 4 shows a schematic diagram of a solid-state battery cell with example materials for various layers;

[0059] Figure 5 A schematic diagram showing another production variant of a solid-state battery cell according to the method for producing a silicon anode-solid electrolyte interconnect according to the invention;

[0060] Figure 6 The structure of a solid-state battery composed of a plurality of parallel-connected solid-state battery cells manufactured in a method is shown. DETAILED DESCRIPTION

[0061] The manufacture of the solid electrolyte 11 generally requires high energy input to produce a crystalline structure with high ionic conductivity. In order to achieve a stable anode structure, the method of the present invention is suitable for applying the anode structure 9 to the solid electrolyte 11 ( Figure 2a ), or applying the solid electrolyte 11 to the current collector 2 having the active layer 9 to form the anode 9 ( Figure 2b ). Rapid annealing, especially flash lamp annealing, can then be used to crystallize the layers of the solid electrolyte with a targeted energy input without severely damaging the anode (see Figure 2b ).

[0062] The method of the present invention advantageously allows the processing of the silicon anode-solid electrolyte interconnect 10 to be carried out in two ways. That is, the multilayer structure 9 as the anode active layer is deposited on the solid electrolyte 11 by a dry process, and then the current collector 2 ( Figure 2a ), or first depositing the multilayer structure 9 as the anode active layer on the current collector 2, and then depositing the solid electrolyte 11 ( Figure 2b ), i.e. in reverse order. The layers are stabilized by rapid annealing. This allows the manufacture of the solid-state electrolyte to be carried out separately from the anode production.

[0063] In the first variant ( Figure 2a ), during the production process, the silicon anode is composed of at least one layer of metal and / or silicon or a mixed system consisting of silicon mixed with at least one metal, which is deposited in the form of particles together with additional layers. Applying the anode 9 directly to the solid electrolyte 11 enables optimal ionic contact with the solid electrolyte 11, which is usually difficult to contact. The process parameters required for this purpose and the annealing process by flash lamp annealing do not have a substantial effect on the existing solid electrolyte 11. Finally, the current collector 2 can be applied to the "solid electrolyte and silicon anode" structure with a suitable layer thickness.

[0064] Due to the manufacturing method of the present invention (see Figure 3), in which the current collector 2 on the anode side can be optimized in terms of conductivity, layer thickness (e.g. 3 μm) and weight, since it does not need to fulfill any load-bearing function. The connection of the current lead requires surface contact, which can be achieved, for example, by rolling a lead sheet of suitable thickness directly onto the anode 9 or onto the anode 9 with metal deposited on the surface to reduce the resistance. The subsequent further deposition of the silicon anode 9 can be additionally achieved independently of the substrate 2. By further depositing the solid electrolyte 11, the cathode 7, the cathode current collector 8 and other battery cell structures by appropriate methods, any desired battery stack ( Figure 6 ). Therefore, the capacity of the solid-state battery 15 can also be easily realized and / or adjusted. This stacking method of anode 9 / solid electrolyte 11 / cathode 7 allows the construction of a highly integrated all-solid-state battery.

[0065] The intermediate layer 16 between the anode 9 and the solid electrolyte 11 (see Figure 4 ) is used for interface engineering, allowing the anode 9 to be applied to the solid electrolyte 11 in a targeted manner without additional cost and complexity.

[0066] Figure 5 A manufacturing variant of a solid-state battery cell 14 according to the method for manufacturing a silicon anode-solid electrolyte interconnect 10 of the present invention is shown. In this exemplary embodiment, the silicon anode-solid electrolyte interconnect 10 and the silicon anode-copper current collector interconnect 20 and the solid electrolyte-cathode-aluminum current collector interconnect and / or the cathode electrolyte-aluminum current collector interconnect 19 are manufactured independently of each other. In order to manufacture or form a solid-state battery cell, the separately manufactured layer combinations 10, 20, 19 are connected to each other by their respective block contacts. In the case of, for example, a silicon anode-solid electrolyte interconnect 10 and a Cu current collector-silicon anode interconnect 20, the block contact refers to the active layer 9, and in the case of a silicon anode-solid electrolyte interconnect 10 and a solid electrolyte-cathode-aluminum current collector interconnect 19, the block contact refers to the solid electrolyte 11. The cathode electrolyte 17 refers to a mixture of the cathode 7 and the solid electrolyte 11.

[0067] The present invention enables the manufacturing sequence of the layers of a solid-state battery cell to be realized in different ways, and the components of the solid-state battery cell can be produced independently of each other with a clear interface and then simply connected to each other in the final process.

[0068] Figure 6The manufacture of the layer stack for a solid-state battery shown in the figure can be carried out according to a first variant of the method for manufacturing a silicon anode-solid electrolyte interconnect 10, in which the active layer 9 of the anode and the current collector 2 are applied to the solid electrolyte 11, or according to a second variant of the method for manufacturing a silicon anode-solid electrolyte interconnect 10, in which the active layer 9 as the anode is applied to the current collector 2 and the solid electrolyte 11 is subsequently applied thereto, or according to a combination of the two variants.

[0069] Applying the silicon anode 9 directly to the solid electrolyte 11 enables the stacking to be completed in a single process, rather than via multiple devices or methods as previously required. This opens up new possibilities for improving performance by influencing the interface in a targeted manner. The number of production devices is reduced.

[0070] Since solid electrolytes (especially solid ceramic electrolytes) are very thick and rigid, the stability required for the anode or solid-state battery cell can be established by the solid electrolyte instead of the current collector of the anode as before. Metal can thus be saved. The focus of optimization can therefore be directed to the electrical contact between the interfaces of the individual battery structures.

[0071] Since the performance of the interface is more critical than the overall performance in solid-state batteries15, the design and manufacturing of the interface become core concerns.

[0072] like Figure 6 As shown, stacking of individual solid-state battery cells 14 is necessary in order to achieve a sufficient total capacity of the solid-state battery 15. Previously, this was not possible because there was no reversible manufacturing of the silicon anode-solid electrolyte interconnect 10 starting from the solid electrolyte 11. This goal was made possible by the planar structure of the solid electrolyte 11, planarization of the anode, rapid annealing, and the use of a dry deposition process.

[0073] Reference numerals list

[0074] 1 Lithium-ion battery

[0075] 2 Anode side current collector

[0076] 3 SEI-Solid Electrolyte Interface

[0077] 4 Electrolytes

[0078] 5 Diaphragm

[0079] 6 Conductive interface

[0080] 7 Positive electrode, cathode

[0081] 8 Current collector on the cathode side

[0082] 9 Anode, cathode, active layer or multilayer structure

[0083] 10 Silicon-anode-solid electrolyte interconnect

[0084] 11 Solid Electrolyte

[0085] 12 Manufacturing sequence 1

[0086] 13 Manufacturing sequence 2

[0087] 14 Solid-state battery cells

[0088] 15. Solid-state batteries

[0089] 16 Interlayer; Artificial Solid Electrolyte Interface

[0090] 17 Catholyte

[0091] 19 Solid electrolyte-cathode-aluminum current collector interconnect and / or cathode electrolyte-aluminum current collector

[0092] Connector

[0093] 20 Silicon anode-copper current collector connector

Claims

1. A method for manufacturing a planar silicon anode-solid electrolyte interconnector (10) suitable for a solid-state battery (15), characterized in that: The multilayer structure is deposited as an active layer of a silicon anode (9) onto a porous solid electrolyte (11) by dry deposition, the multilayer structure (9) is rapidly annealed, and a current collector (2) preferably composed of copper is deposited on the multilayer structure (9).

2. The method for manufacturing a planar silicon anode-solid electrolyte interconnect (10) according to claim 1, characterized in that: An intermediate layer (16) for stabilizing between the solid electrolyte (11) and the active layer of the silicon anode (9) is deposited between the solid electrolyte (11) and the multilayer structure (9).

3. The method for manufacturing a planar silicon anode-solid electrolyte interconnect (10) according to claim 1, characterized in that: The multilayer structure (9) is deposited layer by layer and is formed of at least one layer of metal and / or silicon, or a mixed system consisting of silicon and at least one metal.

4. The method for producing a planar silicon anode-solid electrolyte interconnect (10) according to any one of the preceding claims, characterized in that The metal is formed of at least one of manganese, cobalt, iron, magnesium, titanium, nickel, aluminum, tin, gold and / or silver, and / or a mixture of these materials.

5. The method for producing a planar silicon anode-solid electrolyte interconnect (10) according to any one of the preceding claims, characterized in that The dry deposition method is a PVD process: for example, sputtering or electron beam evaporation.

6. The method for producing a planar silicon anode-solid electrolyte interconnect (10) according to any one of the preceding claims, characterized in that The method steps for manufacturing a planar silicon anode-solid electrolyte interconnector (10) are performed in reverse order, specifically, the multilayer structure is deposited as an active layer on a current collector (2) of a silicon anode (9), preferably on copper, by a dry deposition method, and then controllable and adjustable energy is input into the multilayer structure of the silicon anode (9) for rapid annealing; an intermediate layer (16) is deposited on the multilayer structure (9) for stabilization between the solid electrolyte (11) and the active layer of the silicon anode (9); and a solid electrolyte (11) is deposited, which is rapidly annealed to crystallize the solid electrolyte (11).

7. The method for producing a planar silicon anode-solid electrolyte interconnect (10) according to any one of the preceding claims, characterized in that The energy input into the deposited layers of the multilayer structure (9) and / or the layers of the silicon anode-solid electrolyte interconnect (10) is controlled by means of rapid annealing.

8. The method for producing a planar silicon anode-solid electrolyte interconnect (10) according to any one of the preceding claims, characterized in that The rapid annealing is a flash lamp annealing, which can be performed by flash lamp annealing with a duration of 0.2 to 20 ms and an energy density of 0.3 to 160 J / cm 2 The temperature may be varied by flash lamp in the range of 4°C to 200°C and / or by preheating or cooling in the range of 4°C to 200°C.

9. The method for producing a planar silicon anode-solid electrolyte interconnect (10) according to any one of the preceding claims, characterized in that The rapid annealing is laser annealing, and the annealing time can be set in the range of 0.1 ms to 100 ms by setting the scanning rate of the local heating site and the energy density can be set in the range of 0.01 to 100 J / cm 2 The step of heat treatment may be performed with a laser in a range of 4°C to 200°C, and / or with preheating or cooling in a range of 4°C to 200°C.

10. A planar silicon anode-solid electrolyte interconnect (10) produced by the method according to any one of claims 1 to 9, characterized in that: The solid electrolyte (11) is preferably composed of an oxide material, more specifically, garnet structure oxide, NASICON type phosphate glass ceramic or oxynitride.

11. The planar silicon anode-solid electrolyte interconnect (10) according to claim 10, characterized in that: The solid electrolyte (11) has a crystallinity that results in high ionic conductivity and can be adjusted in a targeted manner by rapid annealing.

12. A solid-state battery cell (14) having a cathode (7) and a planar silicon anode-solid electrolyte interconnect (10) produced by using the method according to any one of claims 1 to 9, characterized in that The silicon anode (9), the solid electrolyte (11) and the cathode (7) have a planar structure.

13. The solid-state battery cell (14) according to claim 12, characterized in that: The cathode (7) is formed of an active layer of LiFePO4, LiMnO2 or LiCoO2, and a current collector (8) preferably composed of aluminum is formed as a cathode on the active layer.

14. The solid-state battery cell (14) according to any one of the preceding claims, characterized in that An anode side structure having a silicon anode-solid electrolyte connector (10) and a silicon anode-copper current collector connector (20) and a cathode side structure having a solid electrolyte-cathode-aluminum current collector connector and / or a cathode electrolyte-aluminum current collector connector (19) can be manufactured and constructed separately from each other, and the silicon anode-solid electrolyte connector (10) and the silicon anode-copper current collector connector (20) and the solid electrolyte-cathode-aluminum current collector connector and / or the cathode electrolyte-aluminum current collector connector (19) are configured in a manner that can be interconnected through respective block contacts (9, 11) in the final manufacturing step.

15. A solid-state battery (15) composed of a plurality of solid-state battery cells (14) according to any one of the preceding claims, wherein the plurality of solid-state battery cells (14) are stacked on one another in a plane and are contacted in parallel and / or in series with one another.